Singularity politics and poetics - Weber, Samuel M. 1940- (University of Minnesota Press, 2021)
"An influential thinker on the concept of singularity and its implications on politics, theology, economics, psychoanalysis, and literature"--
Keywords: Politische Philosophie; Singularität -- Philosophie; Souveränität; Individualität; Particularity (Aesthetics); Other (Philosophy); Individuality; Identity (Philosophical concept); Sovereignty